2015
DOI: 10.7575/aiac.ijkss.v.3n.3p.13
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Skin Surface Temperature after a 10-minute Warm-up on a Bike Ergometer

Abstract: Introduction: Infrared thermography (IRT) is a non-invasive, non-contact procedure for skin surface temperature (SST) diagnostics and represents an effective, safe, and relatively cost-effective diagnosis tool for estimating the SST. While IRT has been established as a diagnosis tool in numerous medical areas of application, it is still in its initial stages as regards to sports science. We will therefore examine the extent to which IRT can be used for diagnosing the SST after a 10-minute warm-up phase. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…No temperature changes were noted by either the subjects or the experimental team. However, as was previously found (Fröhlich et al, 2015 ), increases in skin temperature during the Warmup could explain the identified reductions in MAV int .…”
Section: Discussionsupporting
confidence: 74%
“…No temperature changes were noted by either the subjects or the experimental team. However, as was previously found (Fröhlich et al, 2015 ), increases in skin temperature during the Warmup could explain the identified reductions in MAV int .…”
Section: Discussionsupporting
confidence: 74%
“…A sample size calculation was initially performed with G*Power software (Heinrich-Heine-Universität, Düsseldorf, Germany). The effect size of exercise on skin temperature changes reported in the literature is large [ 23 , 24 ], considering an effect size of 0.4, a statistical power of 0.80, and three repeated measurements for the repeated measures ANOVA assessing the effects of resistance training on skin temperature, a minimum sample size of 12 was calculated. To account for any dropouts and other unforeseen shortcomings, 20 healthy and trained male volunteers aged 25.39 ± 8.21 years (height: 178.88 ± 8.37 cm; weight: 82.38 ± 6.80 kg; BMI: 25.76 ± 1.45) were recruited.…”
Section: Methodsmentioning
confidence: 99%